Factors affecting global quality of milk produced in a semi-arid Algerian steppe zone - Kara, Nabila; Yabrir, Benalia; Laoun, Abbes (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
The purpose of this research was to investigate the effect of the zone, season and collecting point on the quality of milk produced in a semi-arid steppe zone of Algeria. Throughout the four seasons of the year and separated into five zones, this study was done on 334 farms and 25 collectors. It involved 1336 milk samples. The obtained results showed that the physico-chemical and microbiological quality of milk produced in semi-arid zones is influenced by the zone, season, and collecting point. The collecting point behaves similarly to the season, except for pH. They showed a highly significant effect (p ≤ 0.01) for Staphylococcus aureus to a very highly significant one (p ≤ 0.001) for all other physico-chemical characteristics (acidity, density, freezing point, wetting, fat, protein and total solids) and microbiological parameters (thermo-tolerant coliforms, aerobic germs at 30°C, Listeria monocytogenes and Salmonella). On the other hand, the effect of the zone was variable. It is significant (p ≤ 0.05) for Listeria monocytogenes, highly significant for freezing point and wetting, and very highly significant for the other parameters, except for fat content and Salmonella which were not influenced by the zone. Among other things, pH was not affected by the collection point. This variability in milk’s quality is the result of above mentioned factors, either considered independently or in combination. The collection point highlights the mixing effect. The season acts directly through its temperature (condition of transport and storage of milk) or indirectly on the feeding of the animals and the area directly by its climate or indirectly through its plant cover.